A Corpus-Based Analysis of the Pervasive and Effective Metaphor Use in Donald Trump’s 2016 Presidential Campaign - Sifton, Sarah (Satura, 2020)
The language of U.S. President Donald Trump has been the subject of myriad discussions. Many have deliberated on his syntax, lexicon, and oration. Yet, there has been little discussion regarding his use of figurative language,especially metaphors. Therefore, the present study takes a mixed method approach, specifically one of corpus linguistics, concordancing, and critical discourse analysis to analyze the metaphors used in Donald Trump’s 2016 presidential campaign speeches. Furthermore, an investigation into the implications of his metaphor use will also be conducted in order to highlight his underlying ideologies and attitudes.